IRF5 activation in monocytes of SLE patients is triggered by circulating autoantigens independent of type I IFN - Stone, Rivka C. (2012)
OBJECTIVE: Genetic variants of interferon regulatory factor 5 (IRF5) are associated with susceptibility to systemic lupus erythematosus (SLE). IRF5 regulates the expression of proinflammatory cytokines and type I interferons (IFN) believed to be involved in SLE pathogenesis. The aim of this study was to determine the activation status of IRF5 by assessing its nuclear localization in immune cells of SLE patients and healthy donors, and to identify SLE triggers of IRF5 activation. METHODS: IRF5 nuclear localization in subpopulations of peripheral blood mononuclear cells (PBMC) from 14 genotyped SLE patients and 11 healthy controls was assessed using imaging flow cytometry. IRF5 activation and function were examined after ex vivo stimulation of healthy donor monocytes with SLE serum or components of SLE serum. Cellular localization was determined by ImageStream and cytokine expression by Q-PCR and ELISA. RESULTS: IRF5 was activated in a cell type-specific manner; monocytes of SLE patients had constitutively elevated levels of nuclear IRF5 compared to NK and T cells. SLE serum was identified as a trigger for IRF5 nuclear accumulation; however, neither IFNα nor SLE immune complexes could induce nuclear localization. Instead, autoantigens comprised of apoptotic/necrotic material triggered IRF5 nuclear accumulation in monocytes. Production of cytokines IFNα, TNFα and IL6 in monocytes stimulated with SLE serum or autoantigens was distinct yet correlated with the kinetics of IRF5 nuclear localization. CONCLUSION: This study provides the first formal proof that IRF5 activation is altered in monocytes of SLE patients that is in part contributed by the SLE blood environment.